Human‐Induced Climate Change Intensifies Extreme Precipitation Events in Central China's Urban Areas - Yufan Chen; Shuyu Zhang; Hong Wang; Deliang Chen; Junguo Liu (Geophysical Research Letters)
Abstract Understanding the drivers behind extreme precipitation is crucial for predicting and mitigating the impacts of climate change globally, yet it remains little known how anthropogenic factors contribute to these phenomena. This study investigates the impact of human‐induced climate change on circulation patterns conducive to extreme precipitation over the Central Plains Urban Agglomeration in China, a region frequently experiencing severe flooding and home to a dense population with significant economic and agricultural activities. Using advanced techniques such as deep learning and optimal fingerprinting, this study identifies and analyzes the physical mechanisms behind the extreme precipitation. The findings reveal that greenhouse gas emissions play a pivotal role in altering atmospheric circulation patterns, specifically promoting the westward extension of western North Pacific subtropical high and northwestward shift of South Asian High, along with tropical cyclones. These changes enhance moisture transport and convective activity, leading to more frequent and intense precipitation events.